Morphological and molecular characterizations of cereal cyst nematode Heterodera avenae Wollenweber, 1924 from the Czech Republic - Shesh Kumari (Journal of Integrative Agriculture, 2017)
The cereal cyst nematode, Heterodera avenae Wollenweber, 1924, is a major pest of cereal crops throughout the world and causes serious yield losses, especially of wheat. Previous studies have shown that this species is widely distributed in the Czech Republic. In this study, seven populations of H. avenae were molecularly studied, and one population was morphologically described. Three regions (18S, 28S, and internal transcribed spacer 1) of ribosomal DNA were sequenced and the analysis of the 18S gene of six populations did not reveal any variation, whereas the internal transcribed spacer 1 and 28S sequences of six populations differed by only two nucleotides from a population in Žilina. Precise and quick identification of cereal cyst nematodes is important for effective control measures and ribosomal sequence analyses of seven populations in this study will be useful in future phylogenetic studies of Heterodera spp. occurring in the Czech Republic.